Diets of ocelots (Leopardus pardalis), margays (L-wiedii), and oncillas (L-tigrinus) in the Atlantic rainforest in southeast Brazil - Wang, E. (Swets Zeitlinger Publishers, 2002)
Felids play an important role in structuring the prey community, and thus in the dynamics of the plant community in tropical forests. The diets of three species of small cats, Leopardus pardalis (ocelot), L. wiedii (margay), and L. tigrinus (oncilla) were investigated by analysis of scats and regurgitations during a one-year study at Parque Estadual Serra do Mar, Nucleo Santa Virginia, southeastern Brazil. Small non-volant mammals were the most frequent prey in all the diets. The diets of the three cats were similar but although they consumed the same prey items, they showed differential use of them. Ocelots consumed more reptiles than the other species, oncillas preyed on birds and arboreal marsupials, whereas margays were generalists.
Keywords: diet; Leopardus pardalis (ocelot); L. wiedii (margay); L. tigrinus (oncilla); Atlantic rainforest; southeastern Brazil